SCAPE : final version of action components - Silva, Hélder (2014)
This report provides an overview of the suite of software components including existing tools modified to run on the SCAPE platform and new tools developed by the Action Services Components workpackage. Detailed information about how to install and use them is also provided, making it easy to deploy into the SCAPE platform.